Paternal Communities: Social Welfare and Immigration in Argentina, 1880–1930. (10th September 2015) - Bryce, Benjamin
Abstract: This article charts the emergence of several immigrant-run social welfare institutions in Argentina between 1880 and 1930. Using German-language organizations as an illustrative case study, it argues that immigrants played an important role in shaping the system of social welfare in Argentina over a long historical period. It focuses on the autonomy affluent immigrants sought to attain and the ideas about class, gender, and ethnicity they invoked in their pursuit of this goal. The cause of social welfare helped self-proclaimed leaders construct a specific image of their community, solidify gender and class hierarchies, and paternalistically organize workers under their leadership. These actions fostered a place for affluent immigrants within a broader system of social relations in Buenos Aires. In carving out a space for ethnic communities in a domain where the state, the Catholic Church, and Spanish-speaking philanthropists also had influence, German and other wealthy immigrants transcended the individual communities they aspired to care for and helped shape the relationship between community and society.